Biomechanical evaluation of the phases of the triple jump take-off in a top female athlete - Abeer, E. (Journal of Human Kinetics, 2014)
The triple jump is one of two track and field events in which the athlete aims to maximize the horizontal distance jumped. This jump is comprised of 3 take-off phases (hop, step, and jump), each playing an important role, as they require the jumper to tolerate extremely high forces of impact and to maintain a high level of horizontal velocity. The purpose of the study was to investigate the biomechanical characteristics of the 3 take-off phases in the triple jump in a top female athlete. The 3 take-off phases of the top national female triple jumper were videotaped and analyzed using 2D motion analysis. Three cameras (DSR-SR 68) were placed on the lateral sides of the 3 take-off points, to record the motions of the 3 take-off phases. Results indicated that maximum loss of the horizontal velocity was in the hop phase (1.13 m/s), while the maximum braking time was in the jump phase (0.05 sec). The maximum pushing time was in the jump phase (0.10 s), while the pushing time was equal in the hop and step phases (0.05 s). In conclusion, the success of the triple jump is the result of the physical and technical qualities of the jumper. The excessive loss in horizontal velocity during the 3 take-off phases is the main factor limiting the performance of the top female athlete.